Overexpression of mqsR in Xylella fastidiosa Leads to a Priming Effect of Cells to Copper Stress Tolerance - Carvalho, Isis Gabriela Barbosa; Merfa, Marcus Vinicius; Teixeira-Silva, Natália Sousa; Martins, Paula Maria Moreira; Takita, Marco Aurélio; de Souza, Alessandra Alves (Frontiers in Microbiology, 2021)
Copper-based compounds are widely used in agriculture as a chemical strategy to limit the spread of multiple plant diseases, however, the continuous use of this heavy metal has caused environmental damage as well as the development of copper-resistant strains. Thus, it is important to understand how the bacterial phytopathogens evolve to manage this metal in the field. The MqsRA Toxin-Antitoxin system has been recently described for its function in biofilm formation and copper tolerance in Xylella fastidiosa, a plant-pathogen bacterium responsible for economic damage in several crops worldwide. Here we identified genetic mechanisms regulated by X. fastidiosa MqsRA by assessing changes in global gene expression with and without copper. Results show that mqsR overexpression led to changes in the pattern of cells aggregation, culminating in a global phenotypic heterogenicity, indicative of persister cells formation. This phenotype was also observed in wild-type cells but only in presence of copper. This suggests that MqsR regulates genes that alter cells behavior in order to prime them to respond to copper stress, which is supported by RNA-Seq analysis. To increase cellular tolerance, proteolysis and multidrug resistance are induced in presence of copper, in an MqsR independent response. In this study, we show a network of genes modulated by MqsR that is associated with the induction of persistence in X. fastidiosa. Persistence in plant-pathogenic bacteria is an important genetic tolerance mechanism still neglected for the management of phytopathogens in agriculture, for which this work expands the current knowledge and opens new perspectives for studies aiming a more efficient control in the field.